1901 Conn. Pub. Acts 29 - (:unkn) unknown (My University, 1901)
§10: Created a presumption that any person with a gun, trap, or snare on any state game preserve, is in violation of the prohibition of hunting certain animals.
Keywords: HUNTING REGULATION